The Effect of Gender on Stock Price Reaction to the Appointment of Directors: The Case of the FTSE 100 - LUCEY, BRIAN MICHAEL (My University, 2011)
We examine the effect of the appointment of directors on the share price of FTSE companies. We find that the share price reaction to the appointment of Directors suggests that gender is not an issue in the appointment of Non-Executive Directors, but it does have an effect on the market reaction to the appointment of Executive Directors.
PUBLISHED
Keywords: Economics; Business; Gender; FTSE 100; Directors